(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
Analizing the historical relationship between Europe – Italy in particular – and the Far East – represented by the empire of China – is not an easy topic of analysis. Infact, globalization read as a process of economic, cultural, political and technological interdependence has always been in existence, even if conforming to different methods and timing, which makes the discussion wide-ranging and complex. For this reason, the article restricts itself to identifying some moments that may have been definitive in the relationship between the two countries in relation to migration, starting from the ancient Roman Empire and ending with the spread of eighteenth-century chinoiseries, represented by Ferdinando Sanfelice’s ephemeral activity in Naples